The relationship between financial depth, international trade and economic growth in the Philippines - SAPLALA, DINO CARLO (Archīum Ateneo, 2018)
The financial and trade sectors are two sectors which literature saycontribute to economic growth. This study explored the relationship between financialdepth, international trade, and economic growth in the Philippines for the period 1960-2015. The theoretical and empirical framework were derived from Rahman, Shahbaz,and Farooq (2015). Financial depth was measured by an index constructed frombroad money supply per capita, private credit per capita, and deposit bank assetsper capita using principal component analysis. International trade was measuredusing both merchandise exports and imports per capita. Economic growth wasmeasured as real GDP per capita. Using the bounds test of Autoregressive DistributedLag models and the Johansen cointegration test, the study found that there is a longrunrelationship between financial depth, international trade, and economic growth.Using Granger causality tests formulated by Toda and Yamamoto (1995), the studyfound that financial depth and exports per capita lead to economic growth,validating the supply-side hypothesis of financial development and export-led growthhypothesis for the Philippines. These results imply that economic growth in thePhilippines could be promoted by formulating trade policies that increase exports andmeasures necessary to develop the Philippine financial system further.